Lateral root development differs between main and secondary roots and depends on the ecotype - Perotti, María Florencia; Ariel, Federico D; Chan, Raquel Lía (Taylor & Francis Group, 2020)
Root architecture depends on the development of the main root and also on the number and density of lateral roots. Most molecular knowledge about the development of lateral roots was acquired studying primary roots, and it was implied that high order roots follow the same pattern. Recently, we informed that AtHB23 is differentially regulated in primary and secondary roots. Here we show that LBD16, a target of AtHB23, also is differentially regulated; it is expressed in the tip of secondary and tertiary roots but not in primary ones. Moreover, the key hormone auxin exhibits a different distribution pattern in secondary and tertiary roots, according to the reporter DR5. Finally, we show that in Col 0 and Ler ecotypes development of secondary and tertiary roots exhibits significant variations. Altogether, we can conclude that different genetic programs govern secondary and tertiary roots development and such processes are dependent on the Arabidopsis genotype.
Keywords: Raíces (Botánica) - Fisiología; Lateral root